An exploration of work-related experiences of domestic workers in Accra, Ghana. (2nd October 2021) - Hodzi, Matilda Botchway; Annor, Francis; Darkwah, Ernest
Abstract: This study explored work-related lived experiences of domestic workers in the Ghanaian context. Using a qualitative approach, we conducted in-depth interviews with 14 domestic workers in Accra to develop insights into how various characteristics associated with domestic workers' jobs shape their psychological well-being and how they thrive in the face of their experiences. The study revealed that domestic workers face exploitation and abuse, have no written formal work contracts, and enter that kind of work as a means to addressing existential needs. It was further observed that the work situations of domestic workers expose them to potential psychological distress, and many of them use emotion regulation to cope with abuse and exploitation on the job. However, the study also found evidence that domestic workers derive satisfaction from their job when they are given fair employment conditions. These findings suggest the need for policies and interventions targeted at providing psychosocial support and regulating the domestic work sector to safeguard the health and wellbeing of domestic workers.